Study of the external appearance of the flea beetle Longitarsus ballotae Mar. in Iraq (Journal of the College of Basic Education, 2022)
Longitarsus ballotae Mar. It represents the characteristics of the family. The main parts of the body, namely the head, thorax, abdomen and their appendices, were studied in order to evaluate the structures of the external appearance and the extent of reliance on them in the classification of species.